2017
DOI: 10.1080/08037051.2017.1346459
|View full text |Cite
|
Sign up to set email alerts
|

Immune markers, diurnal blood pressure profile and cardiac function in virologically suppressed HIV-infected patients

Abstract: Compromised immune status may contribute to attenuated diurnal BP profile as well as impaired diastolic function in well-treated HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“… 17 Clinical studies report an attenuation of diurnal blood pressure rhythms in HIV-infected patients that may be due to their compromised immune status. 60 , 61 Premature immune aging and non-AIDS-related diseases increase in HIV patients with age. 62 Importantly, rhythmic activities such as sleep/wake patterns change with increasing age, 63 consistent with reports of disturbed sleep in HIV infection 64 , 65 and delayed circadian rhythms in older Africans living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Clinical studies report an attenuation of diurnal blood pressure rhythms in HIV-infected patients that may be due to their compromised immune status. 60 , 61 Premature immune aging and non-AIDS-related diseases increase in HIV patients with age. 62 Importantly, rhythmic activities such as sleep/wake patterns change with increasing age, 63 consistent with reports of disturbed sleep in HIV infection 64 , 65 and delayed circadian rhythms in older Africans living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Stern et al showed intact circadian transcriptional machinery in T cells from HIV infected subjects 20 . Clinical studies report an attenuation of diurnal blood pressure rhythms in HIV infected patients that may be due to their compromised immune status 60,61 . Pre-mature immune aging and non-AIDS related diseases increase in HIV patients with age 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Nondipper pattern was found more frequently in HIV-infected than in non-HIV patients in previous case–control studies. 45,46 In general populations, non-dipper pattern has been associated with psychological and social factors, such as depression and social isolation, or sleeping disorders such as obstructive sleep apnea syndrome or insomnia. Interestingly, these factors are particularly common in HIV-infected population.…”
Section: Discussionmentioning
confidence: 99%